The Self-Character Development : Self-Character Development for KCK High School Students through the Outbound Training Learning Concept - Nasrul Efendi; Sugianta Ovinus Ginting; Naca Perangin-Angin (Universitas Lancang Kuning, 2023)
School as a vehicle for learning plays a major role in developing student character. Cinta Kasih Catholic Private High School is dealing with the condition that some students lack ethics when communicating, are not polite in sponsoring such as interrupting the other person's conversation, like fishing in class, easily influenced by the environment, tend to be picky about friends, lack of commitment in doing group assignments. This community service activity aims to provide a learning method with a different approach, namely by utilizing various forms of games that are packaged according to character education material that will be given to students to make it easier to understand and show clear evidence of the importance of good self-character when facing Challenges in the future in various areas of life. In addition, to measure the success of the Outbound Training activities it also uses a one-group pretest-posttest quasi-experimental approach which aims to find out whether the Outbound Training activities carried out provide an increase in participants' knowledge. Keywords: Character, outbound, training, students